27 TECHNOLOGY AND DEVICE NANOSCALE MOSFETS SIMULATION - T. T. Trung; A. M. Borovik; I. Yu. Lovshenko; V. R. Stempitsky; A. A. Kuleshov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Current-voltage characteristics of MOSFET are obtained by computer simulation and their analysis is performed. The inadequacy of the classical models for simulation of nanoscale structures is revealed, as well as the unsuitability methods of direct quantum description for studies requiring a large number of computer experiments is detected.